Modelling Land Use Land Cover Change in Banyumas Regency Using Remote Sensing Data for Tourism Policy Evaluation - Hernina, Revi; Wicaksono, Arif; Wibowo, Adi; Damayanti, Astrid (Jurnal Geografi Lingkungan Tropik (Journal of Geography of Tropical Environments), 2026)
Tourism is essentially a geographical phenomenon, encompassing the movement and flow of people and spatial distribution patterns relating to land use consumption. The impacts of tourism on LUCC must track and monitor regrading effected to environment and human side. For decades, Banyumas Regency has been known for its famous tourist destinations such Baturaden District and numerous waterfalls. However, the development of tourism infrastructures within its vicinity has sparked complaints from communities, particularly damaged roads and decreasing tourist visits. From environmental perspective, excessive tourism development might cause decreasing natural carrying capacity. Therefore, to provide deeper analysis regarding the current tourism development, this article describes the Land Use/Land Cover Change (LULC) in Banyumas Regency in 2000, 2010, and 2020 based on satellite data analysis using Google Earth Engine (GEE). Sentinel satellite data in 2020 were processed to generate LULC, while Landsat TM 5 data were used to provide LULC in 2000 and 2010. LULC classification was performed using Random Forest with accuracy assessment (Kappa) reach 0.81 for 2000, 0.91 for 2010, and 0.96 for 2010. Furthermore, based on CA-Markov method, the predicted LULCC in 2030 will be 84.28% unchanged and 15.72% change. In addition, several tourism development policies need to be evaluated based on the predicted LULCC in Banyumas Regency in order to avoid disturbance to natural resources.